Improving the Ability to Analyze Intrinsic Elements of Short Stories Through the Application of the Inside Outside Circel (IOC) Learning Model With Student Centered Approach - Femmy Murniati; Dessy Wardiah; Muhammad Ali (Journal of Practice Learning and Educational Development, 2025)
This study aims to: (1) Determine the ability of fourth grade students of SDN 24 Sembawa to analyze the intrinsic elements of short stories through the application of the Inside Outside Circle (IOC) learning model with a student centered approach; (2) Determine the percentage increase in the ability to analyze the intrinsic elements of short stories of fourth grade students of SDN 24 Sembawa through the application of the Inside Outside Circle (IOC) learning model with a student centered approach. This type of research is an action research carried out in 2 cycles and each cycle consists of two meetings. This research was conducted in fourth grade students of SDN 24 Sembawa, Banyuasin Regency. Data collection techniques were carried out through test activities. The results of this study indicate that: (1) Through the application of the inside outside circle (IOC) learning model with a student centered approach, the ability of fourth grade students of SDN 24 Sembawa to analyze the intrinsic elements of short stories can be improved; (2) The percentage increase in the ability of fourth grade students of SDN 24 Sembawa to identify the intrinsic elements of short stories from cycle I to cycle II is 5.92%.